Beliefs about medicine and medication adherence among Malay patients with type 2 diabetes mellitus in primary health care / Mohd Dziehan Mustapa - Mustapa, Mohd Dziehan (2010)
Prevalence of diabetes is increasing all over the world and the number is expected to rise to 300 million in the year 2025 (WHO, 2003). Malaysia is not excluded from this increasing trend; WHO estimated that 2.48 million Malaysians will be diagnosed with diabetes by the year 2030 (Zanariah et. al., 2008). This research aims to investigate the relationship between cognitive and emotional parameters of patients' attitudes and beliefs toward prescribed medicines and medication adherence among Malay Type 2 diabetes mellitus patients in Primary Health Clinics. The specific objectives of this study is to explore Malay Type 2 Diabetes Mellitus patients' beliefs, specifically toward prescribed oral hypoglycaemic medication (OH A); to establish level of adherence toward prescribed OH A based on HbAlc latest result (2009/2010); to describe the beliefs on the necessity of prescribed medications and concerns in taking it; to describe the beliefs about the general harm of the prescribed medications and beliefs that medicines have been overused by the prescribers in general; to analyse the relationship between beliefs about medicine (necessity and concern) with self-reported adherence score (MARS) and finally to investigate the differences in beliefs about medicine among genders, age groups, duration of being diagnosed with diabetes, educational level, and household incomes. In this study, 345 Malay Type 2 diabetes mellitus patients agreed to participate. The results from BMQ-specific showed the mean necessity scale (19.91, SD=3.992) outweighs the concern scale (14.75, SD=4.966). For the necessity-concern differential the mean total score is 5.15 (SD 7.165). The mean for total scores of the MARS scale is 21.77 (SD 2.647). The majority of the patients (70.7%) had a necessity scale which outweighs the concern scale. A statistically significant positive correlation between specific-necessity scale and total MARS score while negative correlation between specific-concern scale and general-harm scale with total MARS score (Spearman Rho p=0.000) emerged. There were statistically significant differences for BMQ-subparts specific-necessity, specific-concern and generaloveruse within age group, educational level, duration of being diagnosed with diabetes and household income. There is no significant difference among gender. The majority of the patients agreed to questions in the BMQ necessity scale, a mixed answer of agree and disagree in the concern scale, disagree in the general-harm scale and agree in the general-overuse scale. Beliefs about prescribed medicine among patients associated with self-report medication adherence were similar with the results from Western countries. Theoretically, this preliminary study has shown a significant relationship between beliefs about medicine and medication adherence; thus both tools (BMQ and MARS) could be applied to daily clinical practice by pharmacists to further enhance their ability to ascertain the level of adherence in correlation with patients' beliefs about their medications.